Atrial fibrillation as risk factor for cardiovascular disease and death in women compared with men: systematic review and meta-analysis of cohort studies. - Emdin, C; Wong, C; Hsiao, A; Altman, D; Peters, S; Woodward, M; Odutayo, A (BMJ Publishing Group, 2016)
Objective To determine whether atrial fibrillation is a stronger risk factor for cardiovascular disease and death in women compared with men. Design Meta-analysis of cohort studies. Data Sources Studies published between January 1966 and March 2015, identified through a systematic search of Medline and Embase and review of references. Eligibility for Selecting Studies Cohort studies with a minimum of 50 participants with and 50 without atrial fibrillation that reported sex specific associations between atrial fibrillation and all cause mortality, cardiovascular mortality, stroke, cardiac events (cardiac death and non-fatal myocardial infarction), and heart failure. Data Extraction Two independent reviewers extracted study characteristics and maximally adjusted sex specific relative risks. Inverse variance weighted random effects meta-analysis was used to pool sex specific relative risks and their ratio. Results 30 studies with 4 371 714 participants were identified. Atrial fibrillation was associated with a higher risk of all cause mortality in women (ratio of relative risks for women compared with men 1.12, 95% confidence interval 1.07 to 1.17) and a significantly stronger risk of stroke (1.99, 1.46 to 2.71), cardiovascular mortality (1.93, 1.44 to 2.60), cardiac events (1.55, 1.15 to 2.08), and heart failure (1.16, 1.07 to 1.27). Results were broadly consistent in sensitivity analyses. Conclusion Atrial fibrillation is a stronger risk factor for cardiovascular disease and death in women compared with men, though further research would be needed to determine any causality.